2013
DOI: 10.1644/12-mamm-a-138.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of forest composition on trophic relationships among mast production and mammals in central hardwood forest

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Therefore, hardwood stand use is consistent with the hypothesis that coyote diet and distribution is associated with prey abundance (Windberg and Mitchell , Mills and Knowlton 1991, Patterson and Messier , Wilson et al ), open‐canopy forest, edge habitats, and landscapes devoid of larger canids (Person and Hirth , Moorcroft et al , Kays et al ). Gillen and Hellgren () analyzed a subset of our camera locations ( n = 30) and found that coyote occurrence was negatively related to the percent basal area of a forest stand composed of hard‐mast bearing trees (e.g., Quercus spp., Carya spp. ), suggesting that the type of hardwood forest may be important to coyote occupancy patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, hardwood stand use is consistent with the hypothesis that coyote diet and distribution is associated with prey abundance (Windberg and Mitchell , Mills and Knowlton 1991, Patterson and Messier , Wilson et al ), open‐canopy forest, edge habitats, and landscapes devoid of larger canids (Person and Hirth , Moorcroft et al , Kays et al ). Gillen and Hellgren () analyzed a subset of our camera locations ( n = 30) and found that coyote occurrence was negatively related to the percent basal area of a forest stand composed of hard‐mast bearing trees (e.g., Quercus spp., Carya spp. ), suggesting that the type of hardwood forest may be important to coyote occupancy patterns.…”
Section: Discussionmentioning
confidence: 99%